Innovations – the Basis Tools of Development of Agricultural and Ecological Management - MORAVSKA, Olena V.; LEVYTSKYY, Taras R.; VELYCHKO, Volodymyr O.; ORLOVA, Olena M.; SHULZHYK, Yuriі A.; SENYSHYN, Svitlana (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).02, 2022)
The article considers the specifics and classification of innovations in the system of agro-ecological management of the agro-industrial complex of Ukraine. Priority directions of development of ecologically oriented innovation projects based on development and improvement of management system and production and technological processes are offered. Methodical developments of introduction of innovation-investment projects of research institutes and recommendations of educational institutions are presented. It is substantiated that the mechanism of intensification of innovations in the agro-industrial complex of Ukraine is a complex process - from research and development, experimental verification of scientific results to introduction into production and evaluation of innovation efficiency taking into account financial, economic, ecological and social spheres. Based on the conducted scientific and methodological work, it was concluded that the growth of the agro-industrial complex of Ukraine can be achieved through the production of competitive products with high added value in compliance with environmental standards in the implementation of innovation - investment projects taking into account the experience of economically developed countries.